(untitled) (Revista Electrónica REDINE, 2021)
GESTIÓN Y GERENCIA (ISSN: 2443-4612), a scientific dissemination medium founded in 2007, is a scientific journal, refereed and indexed, published biannually, open access and free, published in the Research Center of the Dean of Sciences Economics and Business Administration of the Universidad Centroccidental Lisandro Alvarado (UCLA), Venezuela. It is aimed at the publication of collaborations in the field of Social Sciences with special emphasis on management, economic, business, social and community issues. It is currently cataloged in Dialnet, Latindex and Revencyt.